Simulation of Ion Source’s Control System on Cyclotron Using Programmable System on Chip (PSoC) - R.S. Darmawan; S. Santosa; Silakhuddin Silakhuddin (PPIKSN-BATAN, 2011)
Cyclotron is an ion accelerator machine with spiral beam path. Ion source system is one of the main systems which its function is to produce ions that will be accelerated. In order to obtain maximum ion current, the ion source must be equipped with a control system that control mechanical system that will adjust the position of the ion source. The mechanical system able to make adjustment in three different axis, that is x, y and z axis. The mechanical system consists of a stepper motor and a set of gears. The control system using Programmable System on Chip (PSoC) utilizes its user module from the Random Sequence group, that is 8-bit Pseudo Random Sequence Generator (PRS8).For x and y axis, if the stepper motor rotate one rotation that means the support will be pushed or pulled 2.5 mm. While for z axis if the stepper motor rotate one rotation that means the support will be pushed or pulled 0.83 mm. The largest deviation of the stepper motor is 2° with error percentage is 1.09%. The mean value of step of the stepper motor is 2.03 step per second.Received: 20 November 2010; Revised: 07 October 2011; Accepted: 11 October 2011